(untitled) - Gidwitz, Adam (Los Angeles, 2015)
Reimagines the second Star Wars film in which Luke Skywalker trains with Yoda to become a Jedi after a rebel defeat on the ice planet Hoth and battles Darth Vader, who reveals a startling secret to Luke during their duel.
Keywords: Fiction; (Fictitious character); Organa, Leia; Fiction; (Fictitious character); Vader, Darth; Fiction; (Fictitious character); Skywalker, Luke; Good and evil; Good and evil; Skywalker, Luke; (Fictitious character); Juvenile fiction; Juvenile fiction; (Fictitious character); Juvenile fiction; Vader, Darth; (Fictitious character); Juvenile fiction; Solo, Han (Fictitious character); Juvenile fiction; Organa, Leia; Fiction